ω -Fatty acids from Malaysian giant snakehead (Channa micropeltes) fish oil - Omar, Muhammad Nor; Md Yusoff , Nur Shahidatul Ahlam; Zainuddin, Nur Aziyah; Yunus, Kamaruzzaman (Oriental Scientific Publishing Co., 2010)
ω-Fatty acids of Channa micropeltes fish oil was analysed. The lipid from the fish flesh was extracted using Folch method and the fatty acid composition was analysed using GC and GC-MS.It was found that the major constituents of C. micropeltes lipid were palmitic acid (C16:0) (14.1%), docosahexaenoic acid (DHA, C22:6 ω-3) (13.9%) and arachidonic acid (AA, C20:4 ω-6) (11.4%). In addition, the total ω-3 and ω-6 contents were 19.8 % and 16.6% respectively and the ratio of ω-3: ω-6 was 1: 0.9